2007
DOI: 10.1515/cclm.2007.141
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin variants influence development of body mass index and plasma levels of total cholesterol in dialyzed patients

Abstract: Common ghrelin variants may have an effect on changes in biochemical and anthropometric parameters in hemodialyzed patients over time and could be used in the future to plan individualized therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…We have genotyped 995 (out of 1014 collected, 565 males and 449 females,) adult patients (mean age 66.9 ± 12.7 years, CR 97.8%), who were undergoing haemodialysis for at least three months in 27 haemodialysis units across all over the Czech Republic; the centres were selected primarily on the basis of their willingness to participate in the study (Hubacek et al 2007). The most common verified causes of end stage renal failure was diabetic nephropathy (N = 102), chronic tubulointerstitial nephropathy (N = 99) and nephrosclerosis based on hypertension (N = 39).…”
Section: Methodsmentioning
confidence: 99%
“…We have genotyped 995 (out of 1014 collected, 565 males and 449 females,) adult patients (mean age 66.9 ± 12.7 years, CR 97.8%), who were undergoing haemodialysis for at least three months in 27 haemodialysis units across all over the Czech Republic; the centres were selected primarily on the basis of their willingness to participate in the study (Hubacek et al 2007). The most common verified causes of end stage renal failure was diabetic nephropathy (N = 102), chronic tubulointerstitial nephropathy (N = 99) and nephrosclerosis based on hypertension (N = 39).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, TNF-α reduces the concentration of ghrelin, a hunger-stimulating hormone. Administration of ghrelin to healthy volunteers instantly induces hunger [22]. This study showed a slight increase in TNF-α concentration in the C group (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…The present study aimed to understand the association between ghrelin and cardiovascular function by measuring the plasma ghrelin levels of the hemodialysis (HD) patients, continuous ambulatory peritoneal dialysis (CAPD) patients and the control group, by analyzing the correlation between ghrelin and the associated indexes and by exploring the correlation between the plasma ghrelin levels and their corresponding echocardiography indicators in these three groups. A previous study indicates that ghrelin is closely associated with malnutrition, inflammation and atherosclerosis ( 4 ). The study of the correlation between ghrelin and malnutrition with dialysis patients has been reported previously ( 5 ), but the correlation between ghrelin and cardiovascular function in patients with dialysis remains to be assessed.…”
Section: Introductionmentioning
confidence: 99%